Wind farm dynamic effect mitigation on power sharing and stability of MTDC grid through a supplementary controller. (June 2022) - Prasad, Sheetla; Yadav, Omkar; Kishor, Nand
Abstract: Effective and reliable integration of offshore wind farm to AC grid is easily achieved via multi-terminal HV direct current (MTDC) grid network. But the dynamics of wind power put stress on the converter terminals which may deteriorate its performance and life span. Therefore, a suitable control scheme is needed which minimizes the dynamic effect of wind farm power on the MTDC grid. This paper presents a supplementary linear quadratic regression (LQR) based control strategy to minimize the effect of wind farm power variability on dynamic power sharing capability of voltage source converter (VSC) terminals. The feedback gains with penalty weights of LQR control strategy optimizes the performance using linear matrix inequality (LMI) approach. The asymptotic convergence of LQR based controller is derived using the Lyapunov stability theorem. In addition to control design to achieve optimal power sharing in MTDC grid, an independent control is also applied on wind farm to exploit maximum power. This is achievable using sliding mode controller (SMC) on wind farm side. The active power sharing capability and DC voltage regulation with proposed control strategy follows smoothly with negligible oscillations against the dynamics of wind farm power variability and changes in converter terminal reference power. The proposed control approach remains effective to distribute the power flow among un-faulted converters against outage of converter terminals. This control strategy is able to share proportionate power according to converter rating, maintain minimum DC voltage deviation, even with time-varying power flow from the wind farm side. The performance of proposed control strategy is validated on five terminal MTDC system through MATLAB® simulations.